2021
DOI: 10.1007/s42399-021-00749-y
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Systematic Reviews on the COVID-19 Pandemic

Abstract: COVID-19 a systemic inflammation involving multiple organs, affecting all age groups, with high mortality rate, severe adverse outcomes, and high economic burden need to be described. A systematic review of systematic reviews conducted. We searched PubMed, OVID Medline, Cochrane library, COVID-19 resource centers of N Engl. J Med, AHA, and LITCOVID. Certainty of evidences was evaluated by GRADE approach. Meta-analysis according to random effects model was conducted. Seventy-one eligible systematic reviews are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 84 publications
1
49
1
7
Order By: Relevance
“…COVID-19 is a systemic inflammation affecting all age groups, with high mortality rate and severe adverse outcomes. It involves nervous system, blood vessels, lung, heart, liver, gastrointestinal system, kidney, eyes, and other organs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 is a systemic inflammation affecting all age groups, with high mortality rate and severe adverse outcomes. It involves nervous system, blood vessels, lung, heart, liver, gastrointestinal system, kidney, eyes, and other organs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 62.5% of patients (30/32) had daily constant and poorly responsive to headache treatment. The recent study by Magdy et al [ 14 ] has found that most of the patients had headache onset during COVID-19 (57%) with diffuse headache (52.9%), pressing character (40.7%) with a median intensity of 7, a median duration of 6 h, and median frequency of 7 days/week [ 19 ]. In another study by Caronna et al, of 130 patients, 74.6% (97/130) had headache with COVID-19 infection [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased cholesterol levels are associated with high CVD risk in both old 6 and young 7 adults, and a confirmed diagnosis of CVD is a prognostic factor for both mortality and severity in COVID‑19 8 . Therefore, elevated cholesterol may indirectly aggravate the infection severity in COVID-19, and possibly even mortality, by causing cardiovascular disease.…”
Section: Cholesterol Increases Susceptibility To Covid-19 By Causing Atherosclerosismentioning
confidence: 99%
“…Another paradigm of the disease soon emerged: a concomitant immunodeficiency involving among other a (profound) decreased lymphocyte count and an impaired type-I interferon response [ 2 , 3 ]. Lymphopenia occurs in up to 68--80% of patients [ 3 , 4 ], is correlated to severity [ 4 ], and involves all subsets including CD4+ and CD8+ cytotoxic T cells, natural killer (NK) cells, memory and regulatory T cells along with B cells [ 3 , 5 ]. Furthermore, blood mononuclear cells obtained from COVID-19 patients produce lower levels of cytokines upon stimulation than those from septic or nonseptic critically ill patients [ 5 ], consistent with a marked impairment of immune effector cell function.…”
Section: Introductionmentioning
confidence: 99%